Sustainable design concept evaluation (SDCE) - Muhamad Aiman, Mahmud (2016)
The unreliability in the market today and demanding of electronic product by customers makes companies and decision makers to find cost effective and time efficient to improved product development process. As we know, design concept evaluation is a critical part in product development and it is the end of conceptual design. It is related to the final success of product development, because when poor criteria assessment in design concept evaluation can be harm at the later stages. Besides that, the companies start to concerned about the sustainability element which is planet, profit and people. This situation give pressure to R&D engineer to make decision in design concept evaluation and to incorporate sustainability to design product. The objective is to provide an alternative method for aiding a group of a decision makers to effectively decide and evaluate the best choice among a set of alternatives under fuzzy conditions. Another objective is to implement sustainability elements in design concept evaluation. In this project, the method is first work that uses an integrated approach of scale of “Weighting Criteria” and decision-making tools which is modified Rough-Grey Analysis. This project also incorporates with sustainability element that can call it as 3P (profit, people, and planet) in assessing the criteria. The inputs are from voices of customers converted to design criteria and survey using scale of weighting criteria. Quantify and normalize are used in dummy attributes tables and procedures of modified rough-grey. Mapping is used when to incorporate sustainability element and the data is from final value of normalize rough-grey analysis. The benefit is enables the designers to make a better-informed decision which incorporated with sustainability assessment result before finalizing the best design concept. The results can be concluded as the system can help a group of decision makers like R&D engineer to improve the effectiveness, objectivity and sustainability of the design concept evaluation. The system can help both private and government which associated with decision-making process.